Semiotika dalam Lagu Che.r.ry dan Summer Song Karya Yui Yoshioka - Puspita Dewi, Ni Made; Damayanti, Silvia; Budiana, I Made (Humanis; Vol 22 No 4 (2018)DO - 10.24843/JH.2018.v22.i04.p10, 2018)
This research entitles “ Semiotic of che.r.ry and summer song by Yui Yoshioka ”. The purpose of this research is to know the meaning of the song Che.r.ry and summer song . The method choosen for this research is Descriptive Analysis and Informal Method. The theory used is Semiotics Theory by Riffaterre .As the result, The meaning of che.r.ry song is first love . T here is symbolic figure such as sakura (cherry blossom) that symbolized as human, hoshi (star) that symbolized as a wish, and haru (spring) as a sign of time change. The second song is Summer Song that described unexplained love. Beside that, niji (raimbow) that symbolized as someone who being loved, himawari (sun flower) as a loyality, yokaze (night wind) as a situation and name no oto ( voice of wave) as an imajination.